THE ADPF 347 AND THE SYSTEM OF PRECEDENTS (CIPEEX, 2025)
The present study aims to analyze the relationship between prospective temporal efficacy and the system of judicial precedents in Brazil, also addressing the techniques of overruling and distinguishing in binding precedents. To this end, the analysis will focus on the Claim of Non-Compliance with a Fundamental Precept (ADPF) 347, the Collective Habeas Corpus (HC 143.641), and structural injunctions, which aim to halt persistent and prolonged violations of fundamental rights. Subsequently, the study will examine the familiarization of the Roman-Germanic system adopted by Brazil with the institution of these decision-making mechanisms, given that they demand a sophisticated assimilation among the levels of the Judiciary to ensure their effectiveness.
Keywords: precedents; structural injunctions; adpf 347; stare decisis